THE ORIGIN OF QUBA KHANS: NEW VERSION - Eskenderov, Bedirhan Emirulahovic (History, Archeology and Ethnography of the Caucasus, 2019)
The article examines the origin of the rulers of the Quba Khanate, which was located in the North-East of the modern Azerbaijan Republic. A.-K. Bakikhanov in his work "Golestan-e Eram" states that the Quba khans were direct descendants of the yangikent line of the kaitag utsmi, to which the Quba khanate was handed over to the hereditary possession of the Shah of Persia. Basing on the book by Bakikhanov, a well-known scholar-caucasiologist A.P. Berzhe deduced the ancestry of the Quba khans with indication of dates of birth and death of members of their family. The application of the comparative method of studying the sources about the Quba khans and all the peripeteias of their appearance and rule reveals significant differences both in the history of their rule and in the dates of life and death of several members of the khan family with the data given by A. K. Bakikhanov and A.P. Berzhe. As a result of the critical analysis of the sources, it was possible to find out both the controversial nature of the circumstances of the appearance in the Quba territory described in Golestan-e Eram and the failure of Bakikhanov’s theory on the continuous rule of a single dynasty in Quba until the elimination of the khanate by the Russian power in the 19th century. The study revealed that the Quba khanate was ruled not by one but by two dynasties. The first dynasty was of an unknown origin, possibly presented by the people from Kaitag utsmi’s line. However, it was discontinued at the very beginning of the 18th century. The new dynasty was replaced by another one, the ancestor of which, according to legends, was a certain “Lezgi Ahmed”. The second dynasty ruled until the beginning of the 19th century, after which the khans’ rule in Quba was over. Unfortunately, some of the issues of interest remain unanswered, as we could not find any information that sheds light on them.